Uncovering the mechanism linking education expectation and suicide ideation among students in tertiary education: The mediating role of academic burnout, psychache, and hopelessness - Mohammad Izzat Morshidi; Peter K. H. Chew; Lidia Suarez (PLoS ONE, 2025)
High educational expectations are known risk factors for poor psychological well-being and suicide risk among tertiary students. However, the underlying mechanism linking high educational expectations to suicide risk is unclear. Additionally, it is also uncertain if suicide risk due to high expectations is universal or culture specific. The current study proposes a model examining the mediating role of academic burnout, psychache, and hopelessness in explaining the link between educational expectations and suicide ideation. The study also examined the model across samples from Malaysia, Singapore, and Australia to examine cultural variances. The study involved 641 tertiary students from Malaysia, Singapore, and Australia who completed self-report measures on perceived educational expectation, psychache, hopelessness, academic burnout, and suicidal ideation. The model was analysed using path analysis on AMOS 28. Results revealed that academic burnout was not a significant simple mediator, and the mediating roles of psychache and hopelessness across sources of expectations and samples were mixed. Results revealed a significant mediating effect of academic burnout through psychache and hopelessness on suicide ideation for models with self-expectation and parental expectation in all samples. Overall, our study highlights the complex mechanisms underlying the connection between different sources of educational expectations onto suicide ideation among students in higher education.